25. NUTRITIONAL STATUS AND EATING HABITS OF THE FIRST-YEAR AND THIRD-YEAR MEDICAL STUDENTS AT HANOI MEDICAL UNIVERSITY IN 2022-2023 (Vietnam Journal of Community Medicine, 2025)
Objectives: Describe the nutritional status and eating habits of Y1 and Y3 medical students at Hanoi Medical University in the 2022-2023 academic year.Methods: Cross-sectional descriptive study on 520 Y1 (n = 260) and Y3 (n = 260) students. Data were collected through direct interviews and anthropometric measurements. Body mass index (BMI) was classified according to WHO 2007 standards (for Y1) and WHO 2000 (for Y3).Results: The malnutrition rate in Y1 students was 5%, the rate of chronic energy deficiency (CED) in Y3 students was 19.6%. The rate of overweight-obesity (TC_BP) in the two groups was 7.3% (Y1), 6.6% (Y3), respectively. Only 16.9% of the study subjects ate three main meals, 32.5% hardly ate breakfast. The rate of skipping breakfast in women (36.6%) was higher than that of men (29.1%). Male students consumed meat more often than females (p
Keywords: nutritional status; eating habits; medical students; Hanoi Medical University